Dom Pedro Paulo Koop: traços biográficos, atuação no Concílio e a recepção do evento conciliar na Diocese de Lins - Ferreira, Reuberson Rodrigues (2023)
The present research seeks to expose the relationship between the biography of Dom Pedro Paulo Koop, Bishop of Lins, and the process of reception of Vatican II. To reach this objective, the text presents the biographical traces of the character. It points out elements of his family, priestly and religious formation and of his pastoral work in Brazil. The text points out, systematically, the action of the character in the period that preceded the Council, particularly his relationship with the pre-conciliar renovation movements and the consolidation of the bishopric of Bauru. With the election of the religious to the episcopal ministry, it is pointed out his action inside the conciliar assembly, his movements inside the council and his positions defended in this meeting. In the postconciliar movement, under the leadership and the protagonism of this bishop, we seek to demonstrate how the conciliar intuitions, ideas, definitions, and propositions were received in the Linense diocese. In a particular way, elements linked to collegiality, the ecclesiology of the people of God, and human development are evidenced. The perspective of approach of this research is that of literature review and access to sources about the character and the Council